Development of the PD/PI Extended State Observer to Detect Sensor and Actuator Faults Simultaneously - Katherin Indriawati; Trihastuti Agustinah; Achmad Jazidie (IAES Indonesia Section, 2015)
This paper discusses about an observer based faultdetection scheme to detect sensor and actuator faultssimultaneously in LTI system. The proposed strategy is to addderivative action on the extended state observer (ESO) in additionto proportional-integral action, so that the structure of theproposed observer is PD/PI or called PD/PI-ESO. The derivativeaction is performed both in state estimation and fault estimation.This is to achieve fast state estimation as well as fast faultestimation. Furthermore, the effects of disturbance are attenuatedby using the H performance approach. The observer gains arethen determined based on Linear Matrix Inequalities (LMI)technique. Simulation results of a DC motor speed control systemare presented to illustrate the effectiveness of the proposed method.